Fe‐Based Tunnel‐Type Na0.61[Mn0.27Fe0.34Ti0.39]O2 Designed by a New Strategy as a Cathode Material for Sodium‐Ion Batteries. Issue 22 (25th August 2015) - Xu, Shuyin; Wang, Yuesheng; Ben, Liubin; Lyu, Yingchun; Song, Ningning; Yang, Zhenzhong; Li, Yunming; Mu, Linqin; Yang, Hai‐Tao; Gu, Lin; Hu, Yong‐Sheng; Li, Hong; et al.
Abstract : Sodium‐ion batteries are promising for grid‐scale storage applications due to the natural abundance and low cost of sodium. However, few electrodes that can meet the requirements for practical applications are available today due to the limited routes to exploring new materials. Here, a new strategy is proposed through partially/fully substituting the redox couple of existing negative electrodes in their reduced forms to design the corresponding new positive electrode materials. The power of this strategy is demonstrated through the successful design of new tunnel‐type positive electrode materials of Na0.61 [Mn0.61‐ x Fe x Ti0.39 ]O2, composed of non‐toxic and abundant elements: Na, Mn, Fe, Ti. In particular, the designed air‐stable Na0.61 [Mn0.27 Fe0.34 Ti0.39 ]O2 shows a usable capacity of ≈90 mAh g −1, registering the highest value among the tunnel‐type oxides, and a high storage voltage of 3.56 V, corresponding to the Fe 3+ /Fe 4+ redox couple realized for the first time in non‐layered oxides, which was confirmed by X‐ray absorption spectroscopy and Mössbauer spectroscopy. This new strategy would open an exciting route to explore electrode materials for rechargeable batteries. Abstract : A new strategy of through partially/fully substituting the redox couple of existing negative electrodes in their reduced forms is proposed to design the corresponding new positive electrode materials. The power of this strategy is demonstrated through the successful design of new tunnel‐type positive electrode materials of Na0.61 [Mn0.61‐ x Fe x Ti0.39 ]O2, exhibiting a usable capacity of ≈90 mAh g −1 and a high storage voltage of 3.56 V.